Methodology for the waste quantity and quality measurement Case study: 6 sites in Hanoi - Chi, Ngo Kim; Phuong, Dang Ngoc; Tam, Nguyen Minh (VNU Journal of Science: Natural Sciences and Technology; Vol 25 No 3, 2009)
Abstract